Pharmacovigilance of corticosteroids in dermatological diseases - Reddy, Narotham; Parveen, S.; Syed, Allahuddin (International Journal of Advances in Medicine, 2019)
Background: The aim of the study was to conduct the monitoring, detection, assessment and prevention of corticosteroid induced adverse drug reactions in dermatological diseases. Methods: Patient demographic details, past medical, medication history, lab investigations, allergic history were collected patient were followed and data collected every 1 month from the day of patient recruitment. The 1st, 2nd and 3rd follow ups were done, analysis of ADRs was done by using scales at each follow-up. In statistical analysis, data was articulated in percentage. A prospective, interventional study were designed. Results: In present study, author have recruited 40 subjects of which authors categorized ADRs based on different systems. In that 14 (56%) ADRs were identified in cardiovascular system and it was the majorly affected organ system followed by endocrine system 4 (16%). In 40 patients, 25 patients developed ADRs. In these male patients was 14 (56%) and female patients was 11 (44%). In 25, the majorly developed ADR was hypertension 13 (52%) followed by DM 4 (16%). In all ADRs majorly developed due to use of Prednisolone 17 (42%). The developed ADRs majorly in the age group of 41-50 (48%) years followed by 31-40 (16%) and 51-60 (16%). Conclusions: The study found that incidence of ADRs in males was higher than that of the females. Prednisolone was the most common drug associated with the ADRs. Majority of reported ADRs were managed by giving suitable interventions and most of the patients recovered after management.